Projetos pedagógicos para a formação de professores: um estudo comparado das estratégias e práticas em três universidades da Região Sudeste do Brasil - Helena Machado de Paula Albuquerque; Celia Maria Haas; Regina Magna Bonifácio de Araujo (EccoS – Revista Científica)
In this article we have for objective to study comparatively the pedagogical institutional projects of three universities in the Southeast Region of Brazil that are part of the research project called "The meaning of becoming a pedagogue to students taking the new course of Pedagogy (License)". The purpose is to understand how pedagogic projects are pieced together in compliance to curricular directives passed by Resolution CNE/CP 1/2006. Three categories of analysis were set as criteria for the study: a) the meaning of becoming a pedagogue in the pedagogic project; b) the pedagogic project and the curriculum; c) new legislation and the pedagogic project. It was acknowledged that attention to and compliance with legislation is viewed in different ways in each pedagogic project, essentially due to the proposers' conceptions.